Electricity Generation by Shewanella decolorationis S12 without Cytochrome c - Yang, Yonggang; Kong, Guannan; Chen, Xingjuan; Lian, Yingli; Liu, Wenzong; Xu, Meiying (Frontiers in Microbiology, 2017)
Bacterial extracellular electron transfer (EET) plays a key role in various natural and engineering processes. Outer membrane c-type cytochromes (OMCs) are considered to be essential in bacterial EET. However, most bacteria do not have OMCs and various redox proteins other than OMCs exist in the extracellular polymeric substances of biofilms. We hypothesized that these extracellular non-cytochrome c proteins (ENCP) could contribute to EET, especially with the facilitation of electron mediators. This study compared the electrode respiring capacity of wild type Shewanella decolorationis S12 and an OMC-deficient mutant. Although the OMC-mutant was incapable in electricity generation in normal cultivation, it regained electricity generation capacity (26%) when electron mediator (riboflavin) were added. Further bioelectrochemistry and X-ray photoelectron spectroscopy analysis suggested that the ENCP, such as proteins with Fe-S cluster, may participated in the falvin-mediated EET. The results highlighted an important and direct role of the ENCP, generated by either electricigens or other microbes, in microbial EET process with the facilitation of electron mediators.